Sistem Informasi Manejemen Dan Penerapanya Dalam Optimalisasi Pengolaan Data Transaksi Pada PT. Lafiye Mode Indonesia - Kurniawan, Chandra; Bagus Sadewo, Fio; Fairuz Dzulfiqar, Muhammad; Ramdani, Muhammad; Absar Abdallah, Zidan; Reza Pahlevi, Zulfikar; Samsoni (CV. Shofanah Media Berkah, 2024)
A management information system (MIS) is a combination of hardware and software used to collect, process, and store information that is useful for management in making better decisions. This study aims to develop and implement a management information system that can optimize transaction data management at PT. Lafiye Mode Indonesia. The main focus of this research is to evaluate how MIS can improve operational efficiency, reduce inventory storage costs, and enhance the speed and accuracy of transaction data processing. The research methods used include interviews, observation, and literature study. The results show that the implementation of a desktop-based MIS can facilitate the company in conducting sales transactions and data recording, thereby reducing human errors and increasing administrative efficiency. The integration of a Point of Sale (POS) system also helps manage inventory and payments more effectively. In conclusion, this desktop-based cashier application provides a systematic and adaptive framework to improve service quality and company management.